Alternative sources of financing and the sustainability of Cameroonian start-ups - Félix Zogning; Mireille Bityé; Massoussi Ma Goued Samuel Emile (The Journal of Entrepreneurial Finance (JEF), 2022)
The objective of the paper is to assess the contribution of alternative sources of financing to the survival of SMIs through an analysis of start-ups in Cameroon. Our study employs a qualitative multisite case study methodology. Data was collected from both documentary and primary sources. For the primary data, we conducted semidirected interviews with five start-ups operating in four fields of activity (agriculture, health, finance and ICTs) to assess in depth the behaviour of various promoters who have received alternative financing at least once. The results of our manual and automated analysis led to two major findings: firstly, it is possible to identify alternative financing in the environment of Cameroonian start-ups in the form of social capital (help from loved ones, support from elites and families, community fundraisers, tontines) on the one hand, and crowdfunding on the other. Secondly, these two means of alternative financing are significant sources of added value for the survival of start-ups not only through the preparation and precreation activities (social capital) but as important levers in improving the organizational strategies of start-ups (fundraising among individuals and the possibility of marketing through platforms).
Keywords: D85; G23; G24; L25; M13; 650; alternative financing; survival; social capital; crowdfunding; start-ups